Modifikasi Sistem Pemprosesan Data PT PLN (Persero) Gardu Induk Garuda Sakti Menggunakan Software Delphi - M Aldion Rinaldi; Nurhalim Nurhalim; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Currently electricity data increasingly complex due to the increased use and development of electricity consumption , especially in urban areas such as PT PLN ( Persero ) substation Garuda Sakti needed a system that can accommodate the electrical data of complex practical to analyze the needs and uses Delphi software who apply the formula basic electrical measurements is expected to meet the needs of data that were previously managed in Microsoft Office Excel Software Delphi and produce new systems that are easier practical and efficient to PT PLN ( Persero ) Garuda Sakti Substation Keywords : Delphi, System, Electrical Measurement